PERLINDUNGAN HUKUM DAN TINDAKAN PEMULIHAN TERHADAP PELANGGARAN HAK CIPTA KARYA LAGU DAERAH DI INDONESIA BERDASARKAN UNDANG – UNDANG REPUBLIK INDONESIA NOMOR 19 TAHUN 2002 TENTANG HAK CIPTA - Endry Heweningtiyas, Fahmi Mutiara; Yusa Darmadi, A. A. Ngurah (Kertha Semaya : Journal Ilmu Hukum, 2013)
Copyright is a right that provides protection Exclusive Rights to a creator who is able to produce a creation that has authenticity, as defined in article 12 of Act No. 19 of 2002 on Copyright, besides protecting inventions known to the owner of Law - Copyright also protects the shrimp creature of unknown owners, the creation categorized as Traditional Cultural Expressions is one such song. Authors writing in this article title raised the issue of legal protection and recovery actions infringement Act No. 19 of 2002 on Copyright. The method use yuridis normative. The purpose fot this article is for knowing as legal protection and the implementation of recovery actions infringement. The aim of this article is law protection about indonesia national athem songs come from the expresion of national culture. The restoractive action is done by the law efforcement of civil law, criminal law, and administrative law.
Keywords: Traditional, Culture, Protection, Copyright